A descriptive study on the vapor level of methyl methacrylate and the handling practices of MMA by junior and senior clinicians in the UPCD prosthodontics laboratory - Aranzaso, Anedyn J.
Everyday, students, lab personnel, and professors work in UPCD Prosthodontics lab and manipulate methyl methacrylate (MMA) for fabrication of complete or partial dentures and individual trays. They are exposed to an unknown vapor level of methyl methacrylate. A descriptive study was used to assess the vapor level of methyl methacrylate in the laboratory section of UPCD Prosthodontics clinic and to describe the effects of clinicians' practices in handling of methyl methacrylate to MMA vapor levels. Calibrated low flow rate pumps and sorbent tubes with charcoal as sampling medium were used to measure the vapor level of MMA in the laboratory section of Prosthodontics clinic during the second shift of the second semester. A series of four charcoal tubes were utilized for each measuring points with sampling time of 10, 20, 7 and 5 minutes. Junior and senior clinicians in the inner Prosthodontics laboratory were observed during the third shift of the same semester to assess their practice regarding handling of MMA. Through gas chromatographic analysis, results revealed that vapor level of MMA in the four measuring points within the laboratory was 3.68 ppm, 3.15 ppm, 2.05 ppm and 1.86 ppm. Therefore, the vapor level of methyl methacrylate in the laboratory section of UPCD prosthodontics clinic is below the recommended QSHA threshold limit value of 100 ppm. As for the practice of the clinicians, only 42% of those observed have good practice in dispensing, handling, storage and disposal of MMA.